2006
DOI: 10.1515/cclm.2006.258
|View full text |Cite
|
Sign up to set email alerts
|

Analytical performance and clinical utility of the INNOTEST® PHOSPHO-TAU(181P) assay for discrimination between Alzheimer's disease and dementia with Lewy bodies

Abstract: Background: Total tau (T-tau) and b-amyloid (Ab 1-42 ) levels in cerebrospinal fluid (CSF) can differentiate Alzheimer's disease (AD) from normal aging or depressive pseudo-dementia. Differential diagnosis from dementia with Lewy bodies (DLB) in clinical settings is difficult. Methods: The analytical performance of the INNO-TEST ᮋ PHOSPHO-TAU (181P) assay was validated in terms of selectivity, sensitivity, specificity, precision, robustness, and stability. Clinical utility of the assay alone, or combined with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
103
2
7

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 156 publications
(117 citation statements)
references
References 30 publications
5
103
2
7
Order By: Relevance
“…T-tau is considered to be very stable, as several authors failed to find significant differences in T-tau concentrations between samples frozen and thawed once (11,13 ) and in up to 6 freeze-thaw cycles (11,12,16 ), although Schoonenboom et al (11 ) also observed an increase in T-tau followed by a decrease. P-tau 181P , on the other hand, proved to be very stable in the present study, and the small CIs point to a low variability in evolution of P-tau 181P among the different individuals, in accord with the results of earlier studies (10,16,29 ). Zimmermann et al (18 ) found no significant systematic changes of the biomarker concentrations, but did observe increasing unsystematic variation after 3 freeze-thaw cycles, especially for A␤ and T-tau.…”
Section: Freeze-thaw Cyclessupporting
confidence: 91%
See 3 more Smart Citations
“…T-tau is considered to be very stable, as several authors failed to find significant differences in T-tau concentrations between samples frozen and thawed once (11,13 ) and in up to 6 freeze-thaw cycles (11,12,16 ), although Schoonenboom et al (11 ) also observed an increase in T-tau followed by a decrease. P-tau 181P , on the other hand, proved to be very stable in the present study, and the small CIs point to a low variability in evolution of P-tau 181P among the different individuals, in accord with the results of earlier studies (10,16,29 ). Zimmermann et al (18 ) found no significant systematic changes of the biomarker concentrations, but did observe increasing unsystematic variation after 3 freeze-thaw cycles, especially for A␤ and T-tau.…”
Section: Freeze-thaw Cyclessupporting
confidence: 91%
“…No effects of storage at room temperature on P-tau 181P were found in previous studies (10,14,16 ). One study that examined possible differences between storage at 4°C for 4, 24, and 72 h and immediate freezing at Ϫ80°C could not demonstrate an effect (10 ). In conclusion, we found significant differences in A␤ (and P-tau 181P ) concentrations after delayed storage before freezing.…”
Section: Freezing Delaycontrasting
confidence: 58%
See 2 more Smart Citations
“…Clinical inclusion criteria were probable amnestic AD with high level of evidence of AD pathophysiological process, such as determined by Innotest Amyloid Tau Index (IATI) < 0.8 and P-Tau > 60 (an optimal combination of CSF biomarkers that predicts AD with a specificity of 95% and a sensitivity of 85%) (Vanderstichele et al, 2006); presence of a reliable informant; mild dementia severity (Clinical Dementia Rating -CDR of 1) (Morris, 1993); onset of symptoms ranging from 1 to 5 years prior to inclusion; no personal history of neurological or psychiatric disorder; no family history of AD that could suggest autosomal dominant inheritance; no abnormal feature on brain MRI including stroke, more than one ischemic lacuna, and white matter changes on FLAIR, above grade 2 at the Fazecas scale (Fazekas et al, 1987;Gour et al, 2013).…”
Section: Subjectsmentioning
confidence: 99%